2023
DOI: 10.1001/jamapediatrics.2022.5674
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Infant Screen Use, Electroencephalography Markers, and Cognitive Outcomes

Abstract: ImportanceResearch evidence is mounting for the association between infant screen use and negative cognitive outcomes related to attention and executive functions. The nature, timing, and persistence of screen time exposure on neural functions are currently unknown. Electroencephalography (EEG) permits elucidation of the neural correlates associated with cognitive impairments.ObjectiveTo examine the associations between infant screen time, EEG markers, and school-age cognitive outcomes using mediation analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…In addition, we found that screen time at age 1 year affects poorer communication skills at age 2 years. The effects on cognitive function may be partially mediated by reduced activity in the frontal and parietal brain regions . Conversely, screen time at age 2 years affected subsequent motor and personal-social skills.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that screen time at age 1 year affects poorer communication skills at age 2 years. The effects on cognitive function may be partially mediated by reduced activity in the frontal and parietal brain regions . Conversely, screen time at age 2 years affected subsequent motor and personal-social skills.…”
Section: Discussionmentioning
confidence: 99%
“…However, only among the cohort born in 2015, children who were less stimulated, from families with low income, had mothers with lower formal education, and experienced post‐natal depression had higher screen time than their counterparts. For instance, the associations between sociodemographic variables and screen time observed only among those born in 2015 may be attributed to the inclusion of other screens in the assessment for 2015 cohort, and also may indicate that high screen time levels are associated with an environment characterised by limited care and stimulation (Law et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study done in Singapore documented the lack of executive functioning in children who were 8 years and older. These young people had been exposed to heavy screen/social media time from an early age (Law et al, 2023). We in nursing counter the lack of social cognition and the decreased social brain by having our students work in groups, which encourages and facilitates team building.…”
Section: Monique Germain Rn Ms Ctn-a Cnementioning
confidence: 99%